2011
DOI: 10.1128/aem.01820-10
|View full text |Cite
|
Sign up to set email alerts
|

Novel Probiotic Bifidobacterium bifidum CECT 7366 Strain Active against the Pathogenic Bacterium Helicobacter pylori

Abstract: Helicobacter pylori is considered one of the major risk factors underlying the development of gastritis and gastric and duodenal ulcers. Moreover, 50% of the population carries this bacterium, and consequently, when it is detected, eradication of H. pylori is strongly recommended. Regarding the use of probiotics as functional agents, several studies have shown that there is a direct relationship between the addition of certain probiotic bacteria and in vitro inhibition of H. pylori; however, in vivo studies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 49 publications
1
72
0
5
Order By: Relevance
“…The assay emulated conditions and exposure times to which bacteria are subjected during their passage through the stomach and intestinal tract in two stages and was performed as described previously by Chenoll et al (5). Briefly, bacteria were subjected to simulated gastric and pancreatic juices by using pepsin of pig stomach mucous membrane (3 g/liter; Sigma-Aldrich) and pancreatin of pig pancreas (1 g/liter; Sigma-Aldrich), respectively.…”
Section: Cells and Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay emulated conditions and exposure times to which bacteria are subjected during their passage through the stomach and intestinal tract in two stages and was performed as described previously by Chenoll et al (5). Briefly, bacteria were subjected to simulated gastric and pancreatic juices by using pepsin of pig stomach mucous membrane (3 g/liter; Sigma-Aldrich) and pancreatin of pig pancreas (1 g/liter; Sigma-Aldrich), respectively.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…The resistance levels of the strains to different concentrations of biliary salts (0.5%, 1%, 2%, and 3% [wt/vol] Oxgall; Sigma), NaCl (2%, 3%, 6%, 8%, and 10% [wt/vol] NaCl), and pH (3.0, 2.0, and 1.5) were evaluated by monitoring bacterial growth on 96-well plates according to the methods of Chenoll and coworkers (5). Growth was analyzed at 655 nm in a Multiskan microplate reader (Thermo Fisher Scientific).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…ifidobacteria are intensively exploited by the food industry due to the presumed health beneficial effects they exert on the human host (1)(2)(3)(4)(5). However, the molecular mechanisms underlying these proclaimed health-promoting activities are still largely unknown.…”
mentioning
confidence: 99%
“…Indeed, the production of antimicrobials is often regarded a priori as an important trait in the context of bacterial fitness but also in terms of probiotic efficacy. Several probiotic bacteria produce a variety of antimicrobial compounds (e.g., short-chain fatty acids, hydrogen peroxide, nitric oxide, bacteriocins) that may enhance their ability to compete against other GI microbes and which could potentially inhibit pathogenic (disease-causing) bacteria (1,6). Traditionally, bacteriocin production has been an important criterion in the selection of a probiotic strain, albeit that few studies have definitively demonstrated the impact of bacteriocin production on the ability of a strain to compete within the GI tract and/or positively influence the health of the host (9).…”
mentioning
confidence: 99%